SMAC protein expression as a potent favorable prognostic factor in locally advanced breast cancer - Pluta, Piotr; Jesionek-Kupnicka, Dorota; Kubicka-Wołkowska, Joanna; Pluta, Agnieszka; Brzozowski, Kamil; Potemski, Piotr; Piekarski, Janusz; Kordek, Radzisław; Jeziorski, Arkadiusz (Polish Journal of Pathology, 2018)
Preoperative systemic therapy including neoadjuvant chemotherapy (NCT) is standard treatment in locally advanced breast cancer (LABC), the aim of which is to enable a radical surgery and to reduce the risk of local and distant recurrence. It has been established that NCT in LABC may effectively induce apoptosis. The study objective was to assess the role of a proapoptotic second mitochondria-derived activator of apoptosis (SMAC) in LABC. The study group comprised 56 patients with advanced non-metastatic breast cancer (stage IIB –node positive and III), who received NCT followed by surgery and adjuvant treatment. Expression of SMAC protein was analysed using the immunohistochemistry technique in core biopsies sampled from the patients’ breasts before NCT and in surgical specimens collected after completion of NCT. Expression of SMAC was significantly higher in the breast cancer specimens after NCT (p < 0.01). High expression of SMAC in the core biopsy before NCT correlated with a pathological complete remission (pCR, p < 0.01). The patients with a high expression of SMAC in the surgical specimens after NCT had longer DFS. Our study proves a potential role of SMAC expression in LABC as a novel favourable prognostic factor in LABC for pCR and disease-free survival (DFS).